2021
DOI: 10.3389/fonc.2021.739561
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of Immunosuppressive Therapy for Severe Aplastic Anemia Progressing From Non-SAA: Improved Outcome After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Background and AimsThis study aimed at comparing the efficacy and safety of severe aplastic anemia (SAA) cases that had met the criteria for SAA at the time of diagnosis (group A) with SAA that had progressed from non-SAA (NSAA) (group B), both undergoing first-line immunosuppressive therapy (IST). Additionally, group B was compared with SAA that had progressed from NSAA and who had been treated by allogeneic hematopoietic stem cell transplantation (allo-HSCT) (group C).MethodsWe retrospectively compared 608 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recently, a number of studies have compared the efficacy of IST and Haplo-HSCT in treating SAA as first-line options. 1,37 Liu et al 38 retrospectively compared 608 consecutive patients who receive IST or HSCT and found that the estimated 5-year FFS of patients with SAA that progressed from NSAA who underwent MRD-HSCT, MUD-HSCT, or Haplo-HSCT were 73.7% ± 6.3%, 73.1% ± 8.7%, and 80.2% ± 4.7% respectively, which was better than those treated with IST. The estimated 5-year OS of patients with SAA that progressed from NSAA who underwent MRD-HSCT, MUD-HSCT, or Haplo-HSCT were 75.6% ± 6.1%, 76.9% ± 8.3%, and 80.5% ± 4.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies have compared the efficacy of IST and Haplo-HSCT in treating SAA as first-line options. 1,37 Liu et al 38 retrospectively compared 608 consecutive patients who receive IST or HSCT and found that the estimated 5-year FFS of patients with SAA that progressed from NSAA who underwent MRD-HSCT, MUD-HSCT, or Haplo-HSCT were 73.7% ± 6.3%, 73.1% ± 8.7%, and 80.2% ± 4.7% respectively, which was better than those treated with IST. The estimated 5-year OS of patients with SAA that progressed from NSAA who underwent MRD-HSCT, MUD-HSCT, or Haplo-HSCT were 75.6% ± 6.1%, 76.9% ± 8.3%, and 80.5% ± 4.7% respectively.…”
Section: Discussionmentioning
confidence: 99%